2016
DOI: 10.1007/s10096-016-2635-7
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender differences in Clostridium difficile-related hospitalization trends in Madrid (Spain) over a 12-year period

Abstract: This study aimed to analyze temporal trends by gender and age in Clostridium difficile infection (CDI)-related hospitalization rates in the Autonomous Community of Madrid (Spain) over a 12-year period. A population-based cross-sectional study of all hospital admissions with a CDI diagnosis from 2003 to 2014 was carried out. Annual age-specific hospitalization rates were calculated by gender. All the analyses were performed separately for total hospitalizations and hospitalizations with CDI as the primary diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
4
9
0
1
Order By: Relevance
“…Many of the identified risk factors for CDI in our study are similar to known risk factors for CDI in general populations . As in other studies conducted on hospitalised patients, the population of CDI patients with T2DM was predominantly female, had higher number of simultaneous comorbidities and CDI disproportionately affected older patients …”
Section: Discussionsupporting
confidence: 82%
“…Many of the identified risk factors for CDI in our study are similar to known risk factors for CDI in general populations . As in other studies conducted on hospitalised patients, the population of CDI patients with T2DM was predominantly female, had higher number of simultaneous comorbidities and CDI disproportionately affected older patients …”
Section: Discussionsupporting
confidence: 82%
“…The study population was well-balanced regarding baseline characteristics (year of transplantation, age, distribution of disease-specific prognostic factors, and comorbidity scores) in both main subgroups except for more female patients suffering from CDI in the auto-HSCT cohort (64.3% vs. 31.6%). Indeed, a large Spanish study suggests a higher increase of CDI in hospitalized female patients compared to men of the same age (Esteban-Vasallo et al, 2016). However, in the allo-HSCT cohort, the distribution of sex was similar in both CDI and NCDI groups; in agreement, several studies of hematological patients suggested no sex differences (Alonso et al, 2013;Bilgrami et al, 1999;Scappaticci et al, 2017;Trifilio et al, 2013).…”
Section: Discussionsupporting
confidence: 58%
“…Older age in patients is a statistically significant risk factor for C. difficile infection (p < 0.05). The isolation rate of Clostridium difficile was not statistically different between male and female patients (p > 0.05), which is consistent with many other studies [14]. Clostridium difficile infection was identified at all clinics included in the study.…”
Section: Discussionsupporting
confidence: 89%